Síntesis y propiedades térmicas de algunas resinas fenólicas - F M, Alshawi; Razzq K, Abdul; W S, Hanoosh (Innovaciencia, 2019)
Introduction: Phenolic resins have been in use since the early twentieth century and are considered the first class of synthetic polymers to achieve commercial success, moreover phenolic resins continue to succeed and attract special interest in a large range of industrial applications such as adhesives, paints, and composites; because of their unique physical and chemical properties. Materials and Methods: Prepolymers resol resins (RR, RH, RP, and RC) were synthesized by the reaction of phenolic compounds (resorcinol, hydroquinone, phloroglucinol, and catechol) respectively, with formaldehyde at molar ratio phenol/ formaldehyde 1/1.5, using sodium hydroxide as a catalyst. These resins were characterized by FTIR. The curing reaction of these resins was evaluated using differential scanning calorimetry (DSC), while the thermal stability study was evaluated using thermogravimetric analysis (TGA). Results and Discussion:From the results showing that these prepolymers have different curing temperatures and curing energy, while the TGA study showed that the cured resins have decomposition temperature more than 300 ºC, and char residue at 650 ºC more than 60%. Conclusions: These resol resins have different gel times (8-55) min, and viscosities (435-350) mpa.s. The curing temperature of these resin obtained from DSC curves was (120, 129, 105 and 127 °C), while the thermal behavior of the cured resins obtained from TGA curves showed that these cured resin have two decomposition temperatures and the rate of decomposition in the order of RC < RR< .